Hierarchical urchin-like Co9S8@Ni(OH)2 heterostructures with superior electrochemical performance for hybrid supercapacitors. (9th May 2019) - Xu, Qing; Xia, Ping; Xu, Yuyan; Jiang, Deli; Chen, Min
Abstract : The hierarchical core–shell heterostructure of Co9 S8 @Ni(OH)2 with high open channels enables rapid electrolyte diffusion, thus enhancing the electrochemical performance. Abstract : The hierarchical core–shell heterostructure is a promising electrode material for the construction of high-performance hybrid supercapacitors. Here, a novel urchin-like Co9 S8 @Ni(OH)2 core–shell heterostructure was synthesized. The Co9 S8 @Ni(OH)2 heterostructure exhibited high specific capacity of 1307 C g −1 at a current density of 1 A g −1 and good cycling stability with 98.6% retention after 5000 cycles. Moreover, the hybrid supercapacitor fabricated by using the Co9 S8 @Ni(OH)2 heterostructure as the cathode and activated carbon as the anode delivered maximum energy density of 48 W h kg −1 at 800 W kg −1 with good cycling stability of 85% after 6000 cycles. The unique hierarchical heterostructure and the synergistic effect between each component contributed to the remarkable electrochemical performance of the Co9 S8 @Ni(OH)2 heterostructure. These results will encourage researchers to construct high-performance hybrid supercapacitors by using core–shell heterostructure electrode materials.